Kajian Rupa Ornamen Makam Pesarean Sultan Abdul Kadirun di Bangkalan Madura. : Kajian Rupa Ornamen Makam Pesarean Sultan Abdul Kadirun di Bangkalan Madura. - Rizki Oktaviani; Ika Ismurdyahwati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Paramadina, 2022)
The development of the times, gradually has an impact on the erosion of Indonesian culture. This is due to foreign influences and the ignorance of the next generation to recognize the culture of each region. In this regard, with regard to culture as a system, one of which is the religious system, which relates to religious ceremonies, and religious objects or buildings, apart from temples, as well as ancient tombs found throughout the world. the land of the archipelago. The purpose of this study was to determine the results of the visual analysis on the Royal Mausoleum of Madura Barat at Pesarean Sultan Abdul Kadirun in Bangkalan. This study uses qualitative research that uses several research methods that support and help obtain data effectively such as observation and interview methods. With this method the author can find out the results of research analyzing the shape of the ornaments found in the Jinjing Pesarean Sultan Abdul Kadirun, as conveyed by the resource person that the shape of this tote ornament is like a royal crown which symbolizes the existence of a kingdom, and also the form of flora, namely cassava leaves and flower buds. which means simplicity and fertility.